A taxonomical and environmental study of the genus Brachionus (Rotifera: Monogononta) (Pallas, 1776) in Al-Hammer marsh, south of Iraq - Ahmed, Huda K.; Ghazi, Abdulhusein H. (Iraqi Journal of Aquaculture, 2022)
Samples of Rotifera genus Brachionus were collected from Al-Barka and Al-Nagara region in Al- Hammar Marsh, South of Iraq. Remarks on the taxonomy were notes on 6 species of the genus and a monthly density of each species were recorded during the study period from Feb-2006 to Jan-2007.The highest value of total density was 2.78 ind /l recorded in May -2006, whereas the lowest value was 0.01 ind /l and reported in March-2006.